Accuracy of Visual Estimation of Blood Loss in Obstetrics Using Clinical Reconstructions: An Observational Simulation Cohort Study. Issue 1 (22nd March 2023) - Athar, M.W.; Abir, G.; Seay, R.C.; Guo, N.; Butwick, A.; Carvalho, B.
Abstract : ( Int J Obstet Anesth . 2022;50:10359) Postpartum hemorrhage accounts for 27% of worldwide maternal deaths and is defined as blood loss ≥1000 mL or blood loss accompanied by hypovolemia after birth. Visually estimated blood loss (EBL) following delivery remains the most common method of measurement despite it being largely inaccurate. Previous studies reported that accurate and timely hemorrhage diagnosis occurred in a minority (31%) of cases. While delivery mode, distribution or location of blood loss, the patient's cardiovascular status, or experience may impact accuracy, these have not been tested. This study investigated the relationship between these factors, EBL and actual blood loss (ABL) and contributing factors between differences in EBL and ABL.